DSRT, affinity proteomics, and single-cell surface spatial proteomics in patient with acute myeloid leukemia at diagnosis - Erkers, Tom; Kallioniemi, Olli; Lehmann, Sören (Karolinska Institutet, 2026)
The purpose of this study was to investigate the molecular and functional mechanisms underlying resistance to FLT3 inhibitors in FLT3-mutant acute myeloid leukemia, with the goal of identifying predictive markers of response and potential combination strategies to overcome resistance.

This repository contains multi-omic data generated on FLT3 mutant and wild-type AML patients. The datasets consist of selective drug sensitivity scores, soluble protein levels, and spatial proteomics data, along with annotation files linking patient IDs across datasets and drug classifications. Data processing methods and software dependencies are specified for each dataset.

File List:
- sDSS.csv : sDSS table with response to 528 drug perturbations in FLT3 mutant patients.
- sDSS_FLT3i.csv : sDSS table with response to 8 FLT3i in FLT3 mutant and wild type patients.
- olink_NPX.csv : Soluble protein data table for 17 FLT3 mutant patients.
- pixelgen.RData : RData file containing a merged Seurat object with single-cell spatial proteomics data for 6 FLT3 mutant patients.
- annotation.csv : Annotation file for all samples.

Included is also a list of drug classes:
- drug_class.csv

Total size of the dataset is approximately 1.4 GB.

Detta arkiv innehåller multi-omiska data genererade från patienter med FLT3 mutation och vildtyp AML. Data består av selektiva läkemedelskänslighetsvärden, nivåer av lösliga proteiner samt spatial proteomikdata, tillsammans med annoteringsfiler som länkar patient-ID:n mellan olika dataset och läkemedelsklassificeringar. Databehandlingsmetoder och programvaruberoenden är specificerade för varje dataset.

För mer information se beskrivning på engelska.
Läkemedelskänslighet, affinitetsproteomik, samt encellsspatiell ytproteomik från patienter med akut myeloisk leukemi vid diagnos
Functional and molecular drivers of therapy response in FLT3-mutant leukemia
Keywords: Precision Medicine; Precisionsmedicin; Myeloid leukaemia; Myeloisk leukemi; Functional drug testing; Funktionell drogtestning; FLT3; FLT3; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Cell and Molecular Biology; Cell- och molekylärbiologi; Hematology; Hematologi; Cancer and Oncology; Cancer och onkologi